Disentangling Interfirm and Intrafirm Causal Ambiguity: A Conceptual Model of Causal Ambiguity and Sustainable Competitive Advantage - King, Adelaide Wilcox (Academy of Management Review, 2007)
Causal ambiguity is a well-established construct in the strategy literature. Theorists have yet to differentiate and fully refine the construct in ways that clearly demonstrate its influence on sustainable competitive advantage. To address this limitation, I develop a theoretical model that partitions causal ambiguity based on firm boundaries and specifies the organizational implications of this distinction. This model deepens our understanding of causal ambiguity and provides guidance about promising avenues for future research.